KELAYAKAN PENGGUNAAN MEDIA PEMBELAJARAN GEOGRAFI BERBASIS MULTIMEDIA INTERAKTIF SISWA KELAS X (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2016)
This study aims to find out: (1) To determine the feasibility of the use of Geographic-Based Learning Media Interactive Multimedia Power Exogenous material in class X SMA Banyumas 2nd semester of the school year 2013/2014, (2) To determine the effectiveness of instructional media and student interest towards learning when using this instructional media. Samples were students of class X IIS 2 and X IIS 4 SMA Banyumas, determined using simple random sampling technique. Data collection techniques with documentation, questionnaires, and tests. Data analysis technique used is descriptive and percentage gain test. Results of the study are: (1) Summary of the feasibility study media with criteria 90.40%